Community-based enterprise (CBE) export performance strategy: An analysis of Thailand’s entrepreneurial OTOP program - Sitabutr, Vipada; Deebhijarn, Samart (My University, 2018)
The concept of community-based enterprises operated by small entrepreneurial groups involved in export of locally manufactured and produced products has become a globally recognized way to relieve rural poverty and urban flight. However, the factors involved in export performance strategies are less defined and can vary significantly from country to country. Production capacity for export purposes is a great challenge for developing nations, which in turn influences the quality, service standard, and production scale. Also, customer satisfaction with goods and service act as critical components to export performance. It was, therefore, the intent of this study to identify the factors and their interrelationships in Thailand’s globally recognized “One-Tambon, One-Product” (OTOP) government-sponsored export program. The main research instrument, which measured the five latent variables and 26 observed variables was a questionnaire containing a 6-point unipolar scale to measure the opinions of the 500 exporter/manufacturer sample to the survey’s items. To access the measurement model, a confirmatory factor analysis (CFA) was employed using LISREL Version 9.1 prior to the use of a structural equation model (SEM) to analyze the 8-hypotheses model. Results supported similar studies in which it has been determined that product quality plays a key role in the export customer’s trust, which has a positive impact on distribution satisfaction. Top down management policies and pricing strategies, however, appear to be limiting factors to an OTOP exporter’s success. Finally, future focus should be given to Thai OTOP village cluster competitiveness, in which greater emphasis needs to be given to basic management training, leadership skills, product standardization, maintaining uniform output, understanding costs, and cash flows.
Keywords: Microenterprise; OVOP; Product quality; Satisfaction; Trust